2014
DOI: 10.1017/s1368980013003522
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the nutritional content of baby and toddler foods with front-of-package nutrition claims issued by manufacturers v. governments/health organizations

Abstract: Objective: Nutritional information panels are required on all packaged food products in the USA, yet are perceived as difficult to use by consumers. Nutritional symbols have been developed by various groups to assist consumers in making healthier food purchases. Different nutritional criteria are used depending on the authorizing body of these symbols. The present study assesses the nutrient profile of baby and toddler foods in light of their accompanying nutritional symbols. Design: Kruskal-Wallis and x 2 tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Nearly 24 % of all products in our data set bore nutrition references which were unregulated, and unregulated references to negative nutrients were particularly prevalent on foods deemed most processed. While most work examining FOP references on pre-packaged foods has not differentiated regulated and unregulated nutrition information, research conducted on some specific product groups suggests that the presence of an unregulated nutrition reference may indicate a product that is nutritionally inferior to those bearing a regulated claim ( 18 , 19 ) . Insofar as public health authorities see the development of regulated FOP references as both a tool to provide nutritional guidance to consumers and an incentive for manufacturers to reformulate products to achieve better nutrient profiles ( 16 ) , manufacturers’ use of unregulated text merits further study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nearly 24 % of all products in our data set bore nutrition references which were unregulated, and unregulated references to negative nutrients were particularly prevalent on foods deemed most processed. While most work examining FOP references on pre-packaged foods has not differentiated regulated and unregulated nutrition information, research conducted on some specific product groups suggests that the presence of an unregulated nutrition reference may indicate a product that is nutritionally inferior to those bearing a regulated claim ( 18 , 19 ) . Insofar as public health authorities see the development of regulated FOP references as both a tool to provide nutritional guidance to consumers and an incentive for manufacturers to reformulate products to achieve better nutrient profiles ( 16 ) , manufacturers’ use of unregulated text merits further study.…”
Section: Discussionmentioning
confidence: 99%
“…Manufacturer- and third-party-endorsed summary indicator systems and symbols were found on one-fifth of products and appeared in 158 unique formats ( 17 ) . While most research has not differentiated regulated and unregulated FOP references, studies of specific food categories have found 30–60 % of products bearing unregulated text ( 18 , 19 ) . The high density of FOP nutrition references observed on breakfast cereals, mixed dishes, novel beverages and meal replacements ( 17 , 20 , 21 ) suggests that discretionary on-package references to nutrition may be more common on products characterized by a high level of processing.…”
mentioning
confidence: 99%
“…However, some industrialized foods have shown differences between the content of energy claimed on their front label and analyses by a third-party, e.g. a health organization [15,16]. Similarly, the caloric content of the dishes in a restaurant menu may be underestimated by either the individuals or the supplier [17,18].…”
Section: Concept 1 To Avoid or Reduce Overweight And Obesitymentioning
confidence: 99%
“…Positive nutrition references were those that highlighted the presence or addition of a nutrient deemed beneficial (e.g., "good source of calcium", and "high in fibre"). FOP nutrition references were also categorized as being regulated (e.g., nutrient content and disease risk reduction claims) or unregulated, following previous work that suggests that the use of unregulated references may signal lower concentrations of a particular nutrient than is found in a product displaying regulated references (Sacco et al 2013;Metcalfe and Elliott 2015). Regulated nutrition references were identified based on the prescribed wording and permitted wording variations outlined in the Canadian Food and Drug Regulations (Government of Canada 2003) and Canadian Food Inspection Agency's Guide to Food Labelling and Advertising (CFIA 2014).…”
Section: Discussionmentioning
confidence: 99%